Konsumsi Madu Terhadap Kesejahteraan Ibu Postpartum dan Pertumbuhan Bayi: Systematic Literature Review - Ivanda Eka Damayanti; Siti Nurahayu; Nabilah; Retno Widowati; Lisa Trina Arlyn (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The postpartum period is a critical phase for maternal physical and psychological recovery. This study conducted a systematic literature review following PRISMA guidelines to evaluate scientific evidence on the effects of honey on the well-being of postpartum mothers and their infants, including wound healing, breast milk production, sleep quality, mood, and infant growth. Literature searches across five databases (2015–2025) yielded 10 eligible articles, which were thematically analyzed with quality assessment using the CEBM Critical Appraisal Tools. Findings indicate that honey positively contributes to perineal and episiotomy wound healing, increased breast milk production, improved sleep quality, mood stabilization, and reduced fatigue, with effectiveness influenced by maternal nutritional status, regularity of consumption, psychosocial support, and health literacy. Honey has potential as a natural intervention for postpartum mothers, although further research with standardized methodologies is required.